PARTISIPASI MASYARAKAT DAN PERAN UMKM SEBAGAI PENGGERAK EKONOMI DI WATERFRONT KAPUAS PONTIANAK (Universitas Tanjungpura, 2026)
This research was conducted at the Kapuas Pontianak Waterfront tourist area. The objectives of this study were to determine: 1) Community participation in the Kapuas Pontianak waterfront, 2) determine the role of MSMEs as economic drivers in the Kapuas Pontianak waterfront. The research approach used was a qualitative approach with a case study research type. Data collection used observation techniques, interviews in determining informants so that 14 informants were obtained, divided into 1 POKDARWIS person, 1 village person, 6 MSME traders, and 6 visitors, and used several documents relevant to the research. The results of the study found that community participation in the development of the Kapuas Pontianak waterfront tourist area. Through open policies, the community is given the opportunity to open micro, small, and medium enterprises (MSMEs), which play a role in increasing community income and absorbing labor. However, implementation in the field shows various challenges, such as lack of management, informal licensing, and lack of active involvement of the community and managers in decision-making. The results of the study indicate that the tourism sector has had a positive economic impact, but tourism development has not run optimally. Community empowerment strategies and institutional strengthening are needed to realize sustainable tourism.